2007
DOI: 10.1002/ps.1419
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various pyrethroid structures against a highly metabolically resistant isogenic strain of Helicoverpa armigera (Lepidoptera: Noctuidae) from China

Abstract: The findings in this study support the assertion that it is possible to find pyrethroids that are active against resistant populations. Such pyrethroids could be considered as possible partners or resistance breaking pyrethroids in a pyrethroid resistance management programme for H. armigera in China and in other Asian countries where the oxidative metabolism resistance is a dominant mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Results of toxicity studies with the insecticides examined in the present study have also been reported for several pest moth species. Third‐instar larvae of cotton bollworm ( Helicoverpa armigera ) topically treated with beta‐cyfluthrin produced 72‐h LD50s of approximately 4.7 × 10 –2 and 9.9 × 10 –2 µg/g larva (Martin et al 2003; Tan and McCaffery 2007). The 96‐h LD50 value of third‐instar monarchs treated with beta‐cyfluthrin is 1.8 × 10 –2 µg/g.…”
Section: Discussionmentioning
confidence: 99%
“…Results of toxicity studies with the insecticides examined in the present study have also been reported for several pest moth species. Third‐instar larvae of cotton bollworm ( Helicoverpa armigera ) topically treated with beta‐cyfluthrin produced 72‐h LD50s of approximately 4.7 × 10 –2 and 9.9 × 10 –2 µg/g larva (Martin et al 2003; Tan and McCaffery 2007). The 96‐h LD50 value of third‐instar monarchs treated with beta‐cyfluthrin is 1.8 × 10 –2 µg/g.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of P450-mediated resistance to pyrethroids in the YS-FP strain from China was found to depend on the nature of the alcohol moiety in the pyrethroid structure (Yang et al, 2005). Resistance to pyrethroids in the CMR strain from China was also mainly due to enhanced oxidative metabolism, and substitution of the phenoxybenzyl group found in the alcohol moiety of most commercial pyrethroids with a polyfluorobenzyl group (eg in tefluthrin, benfluthrin and transfluthrin) overcame most of the resistance (Tan and McCaffery, 2007). However, esterase-based pyrethroid resistance in an Australian strain of H. armigera was related to the nature of the acid moiety of the pyrethroid structure, being higher for pyrethroids with aromatic acyl groups such as fenvalerate and esfenvalerate (Gunning et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…4-hydroxydeltamethrin was also detected as first degradation product in Tribolium castaneum [ 16 ]. For a strain of a cotton bollworm Helicoverpa armigera with upregulated P450 monooxygenases, Tan and McCaffery showed that structures with polyfluorobenzyl alcohols, lowered the resistance level [ 17 ]. The involved enzymes degrade the infiltrated insecticide and reduce or avoid its effect because only small amounts of the enzyme, if any at all, reach the target receptor.…”
Section: Introductionmentioning
confidence: 99%